Maintenance management of national/state masjids in Malaysia: A preliminary study in Klang Valley - Ibrahim, Md. Najib; Yahya, Mohamad Ridzuan; Abdul Rasid, Anis Azura (2009)
This paper presents the preliminary finding of a study on the building maintenance management of selected national/state masjids in Klang Valley, Malaysia. An evaluation was conducted on the availability of data in terms of information and documentations on maintenance management and the performance of maintenance management. The major maintenance problems were highlighted. The paper concludes that a maintenance management of the masjids was not quite satisfactory.